Arte nossa de cada dia : territorialidades e resistência urbana dos pescadores artesanais na Praia da Penha, Joao Pessoa/PB - Braga, Mirella de Almeida (2023)
In this dissertation, I analyze the right to the city from the Penha neighborhood in João Pessoa/PB, understanding above all the daily and urgent issues of the traditional community of artisanal fishermen, in terms of understanding the fundamental rights and guarantees of the human person according to our Federal Constitution of 1988 and the processes of violations of rights lived in the territory. I emphasize throughout the dissertation that the traditional community of fishermen in the Penha neighborhood, over the years, has experienced processes of speculation in real estate capital that, in a predatory way, triggers the conceptions of poverty/wealth, and leads to the alteration of urban dynamics and overwhelms intermediations with the public authorities in the territory. As a theoretical-methodological contribution, we brought a research aligned with the idea of reflexive sociology by Pierre Bourdieu (2010), as well as the exploratory experiences of a bibliography aimed at discussing the city, people, processes of vulnerabilities. I believe that, along these lines, we have intertwined reflections on the contradictions between equality, territory, diversity, the right to the city and procedures for urban land regularization.